Enhancing Science Learning Outcomes Through a Higher Order Thinking Skills-Based Educational Game on the Solar System - Aprida Singta; I Gde Wawan Sudatha (Thinking Skills and Creativity Journal, 2024)
This study is motivated by the lack of instructional media that can support science learning (IPAS), which has consequently led to low student learning outcomes. The study aims to develop an educational game based on Higher-Order Thinking Skills (HOTS) for science subjects, specifically on the topic of the solar system, and to analyze the validity and effectiveness of the developed product. This research follows a development research design using the ADDIE model. The study participants include subject matter experts, instructional design experts, educational media experts, and students for individual and small-group trials. Data collection methods consist of questionnaires and tests, while data analysis techniques involve quantitative descriptive analysis and inferential statistics. The results indicate that the subject matter expert validation received a score of 100%, instructional design expert validation scored 96%, and educational media expert validation scored 94%. The individual trial obtained a score of 95.33%, while the small-group trial achieved a score of 95.11%. Hypothesis testing results demonstrate a significant difference between students' performance before and after using the HOTS-based educational game on the solar system topic. This finding suggests that the HOTS-based educational game for science subjects is effective in improving student learning outcomes.